Electron Diffusion by Magnetosonic Waves in the Earth's Radiation Belts. Issue 4 (15th April 2022) - Wong, Jin‐Mann; Meredith, Nigel P.; Horne, Richard B.; Glauert, Sarah A.; Ross, Johnathan P. J.
Abstract: We conduct a global survey of magnetosonic waves and compute the associated bounce‐ and drift‐averaged diffusion coefficients, taking into account colocated measurements of f pe / f ce, to assess the role of magnetosonic waves in radiation belt dynamics. The average magnetosonic wave intensities increase with increasing geomagnetic activity and decreasing relative frequency with the majority of the wave power in the range f cp  <  f  < 0.3 f LHR during active conditions. In the region 4.0 ≤  L * ≤ 5.0, the bounce‐ and drift‐averaged energy diffusion rates due to magnetosonic waves never exceed those due to whistler mode chorus, suggesting that whistler mode chorus is the dominant mode for electron energization to relativistic energies in this region. Further in, in the region 2.0 ≤  L * ≤ 3.5, the bounce‐ and drift‐averaged pitch angle diffusion rates due to magnetosonic waves can exceed those due to plasmaspheric hiss and very low frequency (VLF) transmitters over energy‐dependent ranges of intermediate pitch angles. We compute electron lifetimes by solving the 1D pitch angle diffusion equation including the effects of plasmaspheric hiss, VLF transmitters, and magnetosonic waves. We find that magnetosonic waves can have a significant effect on electron loss timescales in the slot region reducing the loss timescales during active times from 5.6 to 1.5 days for 500 keV electrons at L * = 2.5 and from 140.4 to 35.7 days for 1 MeV electrons at L * = 2.0. Plain Language Summary: The modeling and forecasting of the Earth's radiation belts, composed of charged particles trapped by the Earth's magnetic field, is important for mitigating damage to satellites during extreme solar events. Interactions with plasma waves in the magnetosphere can energize and scatter these charged particles, depending on the intensity of the plasma wave and local plasma conditions. One such plasma wave is the magnetosonic wave, which can contribute to both electron energization and loss to the atmosphere. In this paper, we study the role of magnetosonic waves using simultaneous measurements of their intensity and local plasma conditions and find a reduction in the loss timescales of high energy electrons in the near‐Earth region when magnetosonic waves act in combination with other plasma waves. Key Points: Pitch angle diffusion rates for magnetosonic waves exceed those of hiss and VLF transmitters over energy‐dependent ranges of pitch angles Magnetosonic waves have a significant effect on electron loss timescales in the region 2.0 ≤  L * ≤ 3.5 Magnetosonic waves reduce the loss timescales during active times from 140.4 to 35.7 days for 1 MeV electrons at L * = 2.0